Examining the Differential Effectiveness and Efficiency of Alternative Multiplication Drill Interventions with Third-Grade Students. Issue 4 (12th November 2020) - Adams, Sarah R.; Maki, Kathrin E.
Abstract: A large number of students demonstrate difficulty acquiring and retaining math facts highlighting the need for early math intervention. This study used a single-case cumulative acquisition design to examine the differential effectiveness and efficiency of three drill interventions, incremental rehearsal (IR), incremental rehearsal with visual representations (IRR), and traditional drill (TD) for teaching multiplication facts to three third-grade students with multiplication difficulties in a school setting. Results were mixed regarding intervention effectiveness as little differentiation was evident in students' cumulative next day multiplication fact retention across the three intervention conditions. Students made significantly more errors in the TD condition and maintained the most multiplication facts one week after the interventions in the IR condition. TD was the most efficient intervention as students retained the most multiplication facts per instructional minute in this condition, with the IR conditions requiring significantly more time to implement than the TD condition. Implications for intervention practices and future research are discussed.